2017
DOI: 10.1063/1.4980113
|View full text |Cite
|
Sign up to set email alerts
|

BiFeO3-doped (K0.5,Na0.5)(Mn0.005,Nb0.995)O3 ferroelectric thin film capacitors for high energy density storage applications

Abstract: Environmentally benign lead-free ferroelectric (K0.5,Na0.5)(Mn0.005,Nb0.995)O3 (KNMN) thin film capacitors with a small concentration of a BiFeO3 (BF) dopant were prepared by a cost effective chemical solution deposition method for high energy density storage device applications. 6 mol. % BF-doped KNMN thin films showed very slim hysteresis loops with high maximum and near-zero remanent polarization values due to a phase transition from the orthorhombic structure to the pseudo-cubic structure. Increasing the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The energy storage performance of the samples in this study can be expressed by (η, W rev ), for example, (81.3%, 63.7) has been obtained for PZT/AO/PZT opposite double‐heterojunction annealed at 550 °C. The comparison diagram of the energy storage performance is given in Figure for the representative thin films materials, such as polymer thin films, lead‐based thin films, lead‐free thin films . It can be observed that it is difficult to obtain high energy storage density and high efficiency simultaneously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy storage performance of the samples in this study can be expressed by (η, W rev ), for example, (81.3%, 63.7) has been obtained for PZT/AO/PZT opposite double‐heterojunction annealed at 550 °C. The comparison diagram of the energy storage performance is given in Figure for the representative thin films materials, such as polymer thin films, lead‐based thin films, lead‐free thin films . It can be observed that it is difficult to obtain high energy storage density and high efficiency simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Among the currently available electrical energy storage devices, such as batteries, supercapacitors, and dielectric capacitors, the dielectric capacitors exhibit the advantages of fast charge–discharge capability and high power density . According to the different polarization behavior of dielectric materials, the representative dielectric capacitors can be classified as linear dielectric capacitors, antiferroelectric capacitors, and ferroelectric capacitors . Most importantly, energy storage density and energy storage efficiency are two key factors for the performances of energy storage capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…As reported, not only dielectric breakdown but also dielectric polarization is dominant to energy storage performances in dielectrics . Until now, some Bi‐based materials suitable for energy storage were reported by researchers, such as sodium bismuth titanate, bismuth zinc niobate (cubic pyrochlore structure) and BiFeO 3 . Li et al reported recoverable energy storage density of 13.02 ± 0.39 J/cm 3 in 0.9 (Bi 0.5 Na 0.5 )TiO 3 ‐0.1 PbTiO 3 thin film.…”
Section: Introductionmentioning
confidence: 97%
“…The smooth surface of the films is obtained, which is confirmed by few defects and the uniform particle size. Such homogeneous film surface originates from the addition of BMO that inhibits the growth of grain, decreases the grain size, then forms dense surface morphology . This uniform surface is also an important reason for excellent electrical properties.…”
mentioning
confidence: 99%